Methods of Extraction of Cellulose from Bio Waste of Banana Plant and Applications: A Review (Asian Journal of Pharmaceutics (AJP), 2023)
If banana plant waste is not treated, it will be regarded as environmentally hazardous. Therefore, it is essentialto find alternatives to incineration for the disposal of agricultural waste from banana plants. This waste canbe converted into cellulose, which can be used for a variety of biological and pharmacological applications.Therefore, this study briefly outlined the numerous extraction methods that have been used so far on distinctbanana plant components. As cellulose is also accompanied by hemicellulose and lignin along with fats, proteins,and pigments, all extraction techniques used the fundamental extraction stages, such as drying, alkaline treatment,bleaching, and washing with distilled water to achieve neutral pH, to remove this non-cellulosic matter. Thecellulose that was produced would help reduce the overuse of synthetic, non-biodegradable materials. Therefore,the uses of cellulose are discussed, along with the potential biomedical uses of cellulose if it is converted tonanocrystalline cellulose.